Kings & Queens Book III 1603-1714 - Guy, John (Ticktock Publishing Ltd, 1997)
Following the lives of the British Monarchs from 1603 to 1714 this intriguing book highlights the major historic events of the era.
Keywords: Europe; History; Juvenile Nonfiction